Rotating and Accumulating Savings and Credit Associations as Effective Tool for Enhancing the Women Entrepreneurship. A Theoretical Review - Niyonsaba, Benjamin; Adenikinju, Adeola; Ntoiti, Mutuma (European Scientific Journal, ESJ, 2022)
Rotating and accumulating savings and credit associations are recognized as essential drivers for enhancing women’s entrepreneurship. The contribution of the informal organizations on entrepreneurship has been broadly studied. Many have overlooked women entrepreneurship. The current study reviews the theoretical and empirical literature on savings and credit associations and women entrepreneurship. The specific objectives are: to identify factors that encourage women’s participation in rotating and accumulating savings and credit associations, to assess how the rotating and accumulating savings and credit associations promote women’s entrepreneurship, and to establish theories that link rotating and accumulating savings and credit associations and women entrepreneurship. The study is anchored on three theories, namely: social network theory, social capital theory, and theory of structural hole. The research study was based on descriptive research design. The study reviewed previous research on savings and credit groups and women entrepreneurship. Findings showed that thrifts and loans organizations were more effective at augmenting awareness of entrepreneurship among women members than non-partakers. The study concludes that savings and credit organizations have been effective in increasing women’s entrepreneurship. The study recommends the following: First, the savings and credit associations should be included in entrepreneurship development programs of the government. Second, there should be utilization of informal associations as a better approach to have access to microcredits for enterprises startup and growth, and lastly, the inception of programs that will increase awareness of entrepreneurship among women.